Counseling on Clean and Healthy Lifestyles (PHBS) in Rancakalong District, Sumedang, West Java - A. Simarmata, Vidi Posdo; Reviani, Nia; Suryanegara, Wiradi; Langi, Louisa Ariantje; Prihantini, Nur Nunu; Novelyn, Silphia (Asian Journal of Community Services, 2023)
A Clean and Healthy Lifestyle or what is abbreviated as PHBS is one of the efforts or habituation steps for people to achieve a better and healthier quality of life. Extension methods include: presentation by resource persons using a demonstration method, then question and answer discussions and practice on ways to implement PHBS, one of which is washing hands properly according to World Health Organization (WHO) standards. Apart from that, to ensure the position of participants' knowledge regarding PHBS, the PkM team distributed pre and post-questionnaires, where from the results of the questionnaire processing it was found that out of 80 total participants from five villages, 55 participants (69%) experienced an increase in knowledge about PHBS; 20 participants (25%) remained the same and 5 participants (6%) experienced a decrease in scores from pre to post-test.